2016
DOI: 10.4209/aaqr.2015.07.0451
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Properties in Central Kalimantan Due to Peatland Fire

Abstract: The optical properties of aerosol could describe the potential source of prevalent pollutants of certain area. With the annual occurrences of biomass burning over the peat swamp forest, the study of aerosol characters in Central Kalimantan province becomes important. Aerosols from Aerosol Robotic Network (AERONET) data network combine with some environmental parameters, i.e., rainfall, visibility, surface humidity and hotspot number are investigated. Here we use the data from 2012 to 2014 collected from AERONE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 47 publications
2
6
0
1
Order By: Relevance
“…The former feature is clarified by significance and anti-correlations between the PM 2.5 concentration and visibility with r = −0.777; −0.782; −0.740 (p = 0.0001) in Changi, Paya Lebar, and Seletar, respectively. Similar findings by Kusumaningtyas et al (2016) showed a considerable reduction of visibility below 500 m whenever the AOD reached above 3.00 during the biomass burning in Palangkaraya, Central Kalimantan. 3.4.…”
Section: Impact On Visibility In Singaporesupporting
confidence: 73%
See 2 more Smart Citations
“…The former feature is clarified by significance and anti-correlations between the PM 2.5 concentration and visibility with r = −0.777; −0.782; −0.740 (p = 0.0001) in Changi, Paya Lebar, and Seletar, respectively. Similar findings by Kusumaningtyas et al (2016) showed a considerable reduction of visibility below 500 m whenever the AOD reached above 3.00 during the biomass burning in Palangkaraya, Central Kalimantan. 3.4.…”
Section: Impact On Visibility In Singaporesupporting
confidence: 73%
“…This is consistent with numerous studies, which stated that biomass burning is expected to increase AOD. For example, Eck et al (2016) found that during the 2015 fire episode, three AERONET sites in Borneo (Palangkaraya, Pontianak, and Kuching) measured monthly mean fine modes AOD (500 nm) in September and October ranging from 1.6 to 3.7, with the daily average as high as 6.1, which is a similar finding to that of Kusumaningtyas et al (2016). Increase in AOD that coincides with an increase in fire events in Indonesia and southeast Asia was also reported earlier by several researchers (Kanniah and Yaso 2010, Rajab et al 2011, Feng and Christopher 2013.…”
Section: Impact On Visibility In Singaporesupporting
confidence: 66%
See 1 more Smart Citation
“…Episodic and extensive biomass burning in Southeast Asia in recent decades has led to severe local and even significant global effects (e.g., see review in Reid et al, 2013). Especially during drought years when drained peatlands burn (e.g., Field et al, 2009;Heil et al, 2007;Kaiser et al, 2016;Kusumaningtyas, Aldrian Arif Rahman, et al, 2016;Nichol, 1998) the very high concentrations of atmospheric particles has led to significant health effects including possibly several thousand excess mortalities (Crippa et al, 2016). Due to the vast amounts of carbon stored in organic peat soils, partial burning of these peat layers in dry years releases very large amounts of carbon into the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Based on nighttime Raman lidar measurements in Penang Island, for the first time in Malaysia, Hee et al (2016) were able to identify the presence of marine/urban aerosols in the background, irrespective of monsoon seasons, even though wood burning and aged forest fire aerosols prevailed during biomass-burning episodes. Kusumaningtyas et al (2016) reported for the first time that an exceptionally high value (~6) of AERONET/AOT due to peatland fire was observed in 2012-2014 at the Central Kalimantan site (Indonesia), where a high mean-value of single-scatteringalbedo (SSA, ~0.94) also indicates a clear signature of underground smoldering. Furthermore, Qi et al (2016) reported that aerosol optical properties exhibited high value in absorption AOT and high aerosol volumes, low SSA in coarse mode after agricultural burning of rice straw in East China.…”
Section: Remote Sensing Of Air Quality and Impact On Radiative Energementioning
confidence: 99%